Internal carotid artery dissection after laparoscopic surgery - Martín-Mateos,Esperanza (2018)
Abstract Headache is a common symptom in the postoperative period and may be attributable to, dehydration, sleep deprivation, intentional or inadvertent dural puncture during a neuraxial anesthesia technique, from an inhaled anesthetic agent, or from specific surgical procedures, among other etiologies. However, more serious, uncommon and life-threatening conditions as carotid artery dissection can be associated with severe neurologic sequelae in otherwise young, healthy patients. For these reasons, clinicians involved with postoperative patients should be familiar with the presentation and management strategies for this complication.